Autoinflammatory diseases: Mimics of Autoimmunity or part of its spectrum? Case presentation - Kiss, Maria Helena B.; Magalhães, Cláudia Saad [UNESP] (Springer/plenum Publishers, 2008)
Introduction: Autoinflammatory diseases are very rare diseases presenting within a wide clinical spectrum. Recognition of the main clinical features are challenging due to overlapping or mimicking with autoimmune diseases. Discussion: A case series is reviewed to illustrate typical and atypical features and the difficulties of these diagnoses in the low prevalence areas-a typical unrecognized case of familial Mediterranean fever (FMF) in a youngster, an atypical adult case with overlapping of IMF with Behcet disease, and an early presentation of FMF in infant presenting with inflammatory colitis, as well as the overlapping features within the cryopirin diseases spectrum in an 8-year-old boy who presented with systemic onset arthritis. Conclusion: These cases may represent examples of a very puzzling relationship among disorders of innate and adaptive immune systems and inflammation.
Keywords: autoinflammatory disorders; Muckle-Wells syndrome; CINCA/NOMID syndrome; familial Mediterranean fever